1975
DOI: 10.1002/chin.197544009
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: CHARAKTERISTISCHE ROENTGENTEMPERATUR UND WAERMEAUSDEHNUNGSKOEFFIZIENT VON MG2SI

Abstract: Mit Hilfe einer Präzisionsröntgenmethode wird die Temperaturabhängigkeit der Gitterperiode von Mg2Si im Bereich von 20‐300°C gemessen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

1987
1987
1987
1987

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Since y T > 0, this means that" v > 0 and therefore (aw / aT) v 0, i. e. , the explicit contribution tends to decrease the frequency with increasing T. According to a general scheme suggested in reference [5], the fact that q 0.5 is indicative of predominantly covalent bonding. This is consistent with the results of references [12][13][14] and [21,22] where analogous conclusions are reached. On the other hand, the above results are contrary to those of references [23,24] where it was concluded that the bonding is largely ionic.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Since y T > 0, this means that" v > 0 and therefore (aw / aT) v 0, i. e. , the explicit contribution tends to decrease the frequency with increasing T. According to a general scheme suggested in reference [5], the fact that q 0.5 is indicative of predominantly covalent bonding. This is consistent with the results of references [12][13][14] and [21,22] where analogous conclusions are reached. On the other hand, the above results are contrary to those of references [23,24] where it was concluded that the bonding is largely ionic.…”
supporting
confidence: 93%
“…-Corrected phonon linewidths (fullwidth at half maximum) as a function of temperature. The solid lines represent best least square fits to equation (14).…”
mentioning
confidence: 99%
See 2 more Smart Citations